# If a= 2 and b= 7 , find the value of 3a^3 - 3b^2 +4ab.

*print*Print*list*Cite

### 2 Answers

We are given a = 2 and b = 7. We need to find the value of 3a^3 - 3b^2 + 4a.

3a^3 - 3b^2 + 4ab

substitute the values of a and b

=> 3*2^3 - 3*7^2 + 4*2*7

=> 3*8 - 3*49 + 8*7

=> 24 - 147 + 56

=> -67

**The required value of 3a^3 - 3b^2 + 4ab = -67**

Let E= 3a^3 - 3b^2 + 4ab

We need to find the value of E such that a=2 and b= 7

Then, we will substitute with the values of a and b into the expression.

==> E = 3*(2^3) - 3*(7^2) + 4*2*7

Let us calculate the value.

First we will calculate the exponents.

==> E = 3*(8) - 3*(49) + 4*2*7

Now we will multiply.

==> E = 24 - 147 + 56

Now we will add and subtract.

==> E = -67

**Then the value of 3a^3 - 3b^2 + 4ab = (-67).**